The Role of Habits of Mind (HOM) on Student's Mathematical Problem Solving Skills of Primary School - Yandari, Indhira Asih Vivi; Supartini, Supartini; Pamungkas, Aan Subhan; Khaerunnisa, Etika (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
The research aims to describe the role of habits of minds on the student’s mathematical problem solving skills. Habits of mind studied are persisting, metacognition, thinking flexibly, and applying past knowledge to a new situation. The method used in this research is quantitative correlational. Samples were taken as much as 49 fifth grade students at SDN Walantaka 1. Data collection techniques using HOM scale and essay tests. Based on data analysis results obtained average habits of mind score of 68.26 including into medium category and problem solving skills of 53.68 in low category. The results of the regression test on a significant level of α = 0.05 obtained a conclusion that there is a significant influence between habits of mind on the mathematical problem solving, with a contribution of 67.40%. Based on the findings, the habits of mind plays an important role in problem solving and teachers should be able to develop that aspect.